2013
DOI: 10.1016/j.ccr.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Transformation-Associated Changes in Sphingolipid Metabolism Sensitize Cells to Lysosomal Cell Death Induced by Inhibitors of Acid Sphingomyelinase

Abstract: Lysosomal membrane permeabilization and subsequent cell death may prove useful in cancer treatment, provided that cancer cell lysosomes can be specifically targeted. Here, we identify acid sphingomyelinase (ASM) inhibition as a selective means to destabilize cancer cell lysosomes. Lysosome-destabilizing experimental anticancer agent siramesine inhibits ASM by interfering with the binding of ASM to its essential lysosomal cofactor, bis(monoacylglycero)phosphate. Like siramesine, several clinically relevant ASM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
309
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(328 citation statements)
references
References 44 publications
16
309
0
3
Order By: Relevance
“…Although unexpected with respect to reduced SM levels in cancerous compared to normal tissue (Hendrich and Michalak, 2003;Barceló-Coblijn et al, 2011), ASM activity is down-regulated in cancer (Petersen et al, 2013) and may consequently sensitize these cells to further decreases in enzyme activity levels. Lysosomal stability and integrity requires L-ASM activity (Kirkegaard et al, 2010), while the cytoprotective properties of ASM down-regulation in cancer cells are assumed to relate to the secreted form required for vesicle and membrane turnover (Magenau et al, 2011).…”
Section: Involvement Of Asm In Other Cellular Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although unexpected with respect to reduced SM levels in cancerous compared to normal tissue (Hendrich and Michalak, 2003;Barceló-Coblijn et al, 2011), ASM activity is down-regulated in cancer (Petersen et al, 2013) and may consequently sensitize these cells to further decreases in enzyme activity levels. Lysosomal stability and integrity requires L-ASM activity (Kirkegaard et al, 2010), while the cytoprotective properties of ASM down-regulation in cancer cells are assumed to relate to the secreted form required for vesicle and membrane turnover (Magenau et al, 2011).…”
Section: Involvement Of Asm In Other Cellular Processesmentioning
confidence: 99%
“…While the ASM/ceramide pathway has been well established as a bona fide system in the chemotherapeutic treatment of cancers and many commonly used chemotherapeutic agents mediate cell death via ASMinduced ceramide formation [reviewed in Henry et al, (2013)], recent evidence (Don et al, 2014) suggests that reducing ASM activity with functional inhibitors such as desipramine may induce lysosomal rupture in cancer cells (Petersen et al, 2013). Although unexpected with respect to reduced SM levels in cancerous compared to normal tissue (Hendrich and Michalak, 2003;Barceló-Coblijn et al, 2011), ASM activity is down-regulated in cancer (Petersen et al, 2013) and may consequently sensitize these cells to further decreases in enzyme activity levels.…”
Section: Involvement Of Asm In Other Cellular Processesmentioning
confidence: 99%
“…102,103 Another form of lysosomal cell death where inhibition of acid sphingomyelinase (ASM) enhances membrane permeabilization and destabilization of cell lysosomes has also been reported. 104 Pyroptosis is a caspasedependent form of programmed cell death that differs in many respects from apoptosis. It is an inflammatory type of cell death and unlike apoptosis, depends on the activation of caspase-1 or caspase-11 (caspase-5 in humans).…”
Section: Non-apoptotic Pathwaysmentioning
confidence: 99%
“…34,41 Structure-activity studies have revealed the important role of the C-2 amino group in GAELs as it affects cytotoxicity. 39,43 Some cationic amphiphilic drugs (CADs) have also been shown to induce non-apoptotic lysosomal cell death, 104 perhaps, due to their amphipathic nature. In addition, several cationic amphiphiles have been proposed to have membranolytic mode of action, which may possibly explain their selectivity towards cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…A clearly protective role of inhibition of macrodomain formation was recently shown in irradiation-induced mortality (54). Otherwise, non-lysosomal sphingomyelinase can protect against cytotoxic agents (55).…”
Section: Acknowledgmentsmentioning
confidence: 99%